Strategies of Learning Starts with a Question; Upaya Guru dalam Meningkatkan Hasil Belajar Siswa - Muhammad Munif; Muhammad Kholil; Erica Prasetya Putri (LP2M STIT Palapa Nusantara, 2022)
This study discusses the implementation of the learning strategy learning starts with a question in improving the learning outcomes of fifth grade students at MI Mambaul Ulum Alassumur. This research uses a qualitative case study approach. There were three informants in this study, namely Lailatul Mukarromah as the principal, Vindi Rif'atus Sholehah as a teacher and homeroom teacher for class V, and Dania as a class V student at MI Mambaul Ulum Alassumur. Data analysis is carried out with data collection, data reduction, data display, and conclusions. The research results obtained are the implementation of the learning strategy learning starts with a question in class V, which is carried out in several stages including choosing teaching sources, dividing students into several groups, choosing teaching materials or materials, starting learning by instructing students to read teaching materials then followed by formulating questions, and evaluating learning with questions and answers.